(untitled) - Ruth Gairn (Oxford, 2008)
See how the words are used in spoken and written English. Practise using the vocabulary. Revise what they have learned. Study at home or in class. Learn the words as preparation for major exams. Use the 'test yourself' card to check which words and phrases they know, and which ones need more practice
Keywords: English language,Ngôn ngữ Anh